Pelarangan Pegawai Negeri Sipil Wanita Menerima Poligami Prespektif Maqashid Syariah - Ramadhani, Salmaa Al Zahra (Faculty of Sharia and Law Universitas Islam Nahdlatul Ulama, 2024)
Maqashid Sharia is the realization of the maker of sharia and law that can be taken from the value or meaning of sharia texts that have been studied by scholars and find the meaning and wisdom of sharia law that applies to get the benefits and benefits of the regulations that have been carried out. This research method uses normative legal research by finding an answer to various kinds of problems based on normative logic which is not only based on statutory regulations. This study discusses the prohibition of women who are civil servants to become second / third / and fourth wives in Government Regulation Number 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants as a control of the lives of civil servants in the midst of society with the needs and demands of life faced and a way to prevent family problems among State officials such as divorce, infidelity and polygamy, so this regulation will help the State in controlling the behavior of its employees.